CORPORATE GOVERNANCE - IMPACT ON FINANCIAL PERFORMANCE OF SELECTED IT COMPANIES IN BENGALURU CITY - Sekhar, Mr S.Chandra; Dr. D. Ashalatha,; Gorkhe, Dr.Monika (The journal of contemporary issues in business and government, 2022)
Corporate governance norms in India have evolved well over the year’s post-economic liberalization, with SEBI constituting a number of committees to suggest codes of conduct for good governance of corporate organizations. Corporate governance has received much attention in the accounting literature, with studies focusing on the influence of corporate governance on corporate financial performance in selected companies in Bangalore city. The association between quality of corporate governance and firms' profitability is quite major focus in corporate governance improvement. Better governed firms might have more efficient operations, resulting in a higher expected future management. The purpose of this study was to determine the influence of corporate governance on corporate financial performance in selected companies in Bangalore city. Primary data collected through structured questionnaire from selected IT companies (Tech Mahindra, TCS, Infosys, Cap Gemini, Caterpillar, and Wipro) in Bangalore city. Study found that there is a positive correlation between corporate board size, corporate board composition, corporate policy, corporate independent committees and corporate financial performance. The study concluded that Organization should choose a sizeable board which is efficient and well informed in matters corporate governance so as to strengthen their corporate financial performance, organizations should have anexcellent board composition full of individuals with diverse expertise and knowledge so as to enhance better corporate governance.